Interrogating the motivation mechanisms and claims of asset-based community development with self-determination theory. Issue 4 (8th August 2022) - Cunningham, Ian; Willetts, Juliet; Winterford, Keren; Foster, Tim
ABSTRACT: This article uses Self-Determination Theory (SDT) to assess the motivational mechanisms and claims of asset-based community development (ABCD). The limited academic literature argues ABCD's focus on existing assets and locally identified priorities motivates communi-ty participation. However, motivation is only superficially understood and remains unquali-fied. SDT is an established theory of motivation, which we suggest is largely compatible with ABCD. Using SDT as a framework, we determine how common ABCD tools support more autonomous motivations. We also outline how SDT tools and concepts can be inte-grated into ABCD practice and used to evaluate the motivational claims of ABCD-based programs. The findings show SDT can strengthen the theoretical base, practice and evaluation of ABCD interventions.